High-Yielding Dairy Cows - Simões, João Carlos Caetano (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The milk industry is largely based on dairy cattle production. After decades of great advancements in genetics, nutrition, and management, today, one cow can reach unprecedented levels of milk production. New challenges have been posed to preserving the health and welfare of these domestic animals. "High-Yielding Dairy Cows" is a collection of scientific papers focusing on three main areas: metabolic diseases, reproduction diseases, and herd (heath) management in confined and pasture production systems. This book aggregates knowledge from a molecular level to a more holistic approach on disease prevention and management, giving the reader an accurate overview of the current state of the art of this topic. It intends to contribute to ensuring the supply of ethical and responsible animal protein for about eight billion of people.